CAREGIVER STRESS THEORY MAY EXPLAIN ELDER ABUSE BUT NOT NEGLECT IN DEMENTIA FAMILY CAREGIVING. (11th November 2018) - Pickering, C; Yefimova, M; Maxwell, C
Abstract: The caregiver stress theory is suggested as a causal theory for physical and psychological elder abuse (EA) and neglect within dementia, due to the high rate of behavioral symptoms of dementia (BSD) and caregiver stress. The purpose of this micro-longitudinal study is to evaluate the caregiver stress theory among a sample of dementia family caregivers who co-reside with their care-recipient. Participants completed online diary surveys for 21 days. Using multi-level modeling of diaries (N=681) nested within participants (N=46), BSD behaviors (aggressive and non-aggressive agitation) and perceived stress were examined as predictors of EA and neglect. On days with non-aggressive BSD behaviors compared to no BSD, the odds of self-report EA were 2.5 times greater (CI 1.04–5.89, p = 0.03), while on days with both non-aggressive and aggressive BSD the odds of EA were 26.9 times greater (CI 9.62–75.15, p < 0.001). For neglect, non-aggressive BSD alone did not increase risk but when they co-occurred with aggressive BSD the odds increased by 5.3 (CI 1.7–16.71, p < 0.001). For every point a caregiver scored their perceived stress above their typical stress rating, the odds of EA increased by 1.9 (CI 1.37–2.55, p < 0.001), however the risk of neglect did not. This suggests support for the caregiver stress theory as an explanation for EA, as both BSD and perceived stress increased the risk. However, neglect may be driven by a different causal mechanism, as only certain BSD combinations increase odds of neglect.